2021
DOI: 10.1002/ep.13688
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment for hydrothermal carbonization of urban organic solid waste in comparison with gasification process: A case study of Southern Chile

Abstract: Most developing countries lack sufficient legal and management infrastructure to dispose of urban solid waste (USW). The continuous increase of USW generation requires evaluating different treatments for developing countries based on the life cycle assessment methodology to compare the environmental impact by reducing greenhouse gases and leachate. Hydrothermal carbonization (HTC) and gasification processes are presented as potential solutions for USW treatment due to their efficiency in producing energy for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…The study revealed that, depending on the accounting rules, the effect outcomes might vary greatly and can lead to opposing conclusions for some impact categories. Corvalán et al [100] performed a comparative LCA analysis on the hydrothermal carbonization (HTC) of urban organic solid waste and gasification process. Upon evaluating the conversion of 1 ton of organic fraction USW, the results indicated that gasification performed better than HTC.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that, depending on the accounting rules, the effect outcomes might vary greatly and can lead to opposing conclusions for some impact categories. Corvalán et al [100] performed a comparative LCA analysis on the hydrothermal carbonization (HTC) of urban organic solid waste and gasification process. Upon evaluating the conversion of 1 ton of organic fraction USW, the results indicated that gasification performed better than HTC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Corvalán et al conducted a life cycle analysis of thermal treatment technologies for solid energy production in a municipality in southern Chile. [386] They found that the energy yield of the HTC process was higher than that of the gasification process.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…Among these applications, LCA studies applied TRACI for gasifying forestry residue and organic municipal solid waste in the USA (Figure b and Table S10). ReCiPe was employed for LCA studies (with agricultural and forestry residue as feedstocks) in South Africa and Latin American regions (e.g., Brazil, Ecuador, Columbia) in addition to using LCOE for LCCA/TEA. Generally, LCCA/TEA of gasification was conducted in fewer studies compared to LCA in the reviewed literature, where the common methods for LCA were TRACI in USA, CML and IPCC in European and Asian Countries, and ReCiPe in the remaining countries.…”
Section: Applications Of Data Science In Rrcc From Organic Waste Streamsmentioning
confidence: 99%
“…Further, utilizing commercial process simulation tools for such purposes are considered costly, computationally expensive, and lack reproducibility, which can be overcome using ML integrated LCA and LCCA/TEA . Additionally, although not in the scope of this study, it may also be beneficial to consider quantifying social acceptabilities of implementing RRCC, particularly in urban contexts. ,,, One study assessed the social impacts of implementing anaerobic digestion in an animal farm in a rural context through a stakeholder perception study . Apart from such qualitative approaches, a quantitative approach can be the Guidelines for Social Life Cycle Assessment of Products .…”
Section: Toward An Integrated Data Science Approach To Inform Sustain...mentioning
confidence: 99%